Pengaruh Teknik Skimming Terhadap Kemampuan Membaca Cepat Siswa pada Pembelajaran Bahasa Indonesia Kelas IV SD Negeri 104185 Sei Semayang - Ginting, Ririn Vidiani; Ramadhani, Mastari; Harahap, Syarifah Ainun (Medan Resource Center, 2024)
This study aims to analyze the effect of using the speed reading method on the reading speed ability of fourth-grade students at SD 104185 Sei Semayang. The Skimming technique is a crucial skill that enables students to quickly filter essential information and enhance their comprehension of reading materials. This research employs a quantitative approach with an experimental method. The study subjects consist of 33 fourth-grade students. The findings indicate that the use of the Skimming technique significantly influences students' reading speed ability. This is evidenced by the comparison of pretest and posttest scores, where the average pretest score for effective reading speed (KEM) was 90.50, categorized as moderate. After implementing the speed reading method, the average posttest score increased to 144.61, classified as high. Additionally, the results of the t-test analysis showed that the t-value (tcount = 5.722) exceeded the critical t-value (ttable = 3.622), leading to the rejection of H0 and acceptance of H1. These findings confirm that the speed reading method significantly enhances students' reading speed ability at SD 104185 Sei Semayang. Therefore, this method can be effectively utilized as a teaching strategy to improve elementary students' reading skills.